ANALISIS KEBERLANJUTAN PROGRAM PRO-BEBAYA DI KOTA SAMARINDA PASCA PILKADA 2024 - Sultan, Muhammad (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2023)
This study aims to describe and analyze the safety behavior of residents towards emergency disaster mitigation efforts around the Samarinda Fuel Terminal. This research was conducted using a quantitative descriptive method. The population is all heads of families in the RT 27 area of Teluk Lerong Ulu Village as many as 44 people and all of them are used as research samples (total sampling). Data collection was carried out on June 1-20 2023 by direct interview method using a questionnaire with a closed list of questions. The results of the study obtained information that most residents stated the importance of installing evacuation routes in disaster-prone environments such as fire hazards, residents stated that evacuation route signs should be installed using materials that are not flammable and not easily damaged and are willing to take part in disaster simulation activities and maintain Evacuation sign facilities that have been installed at this time.